Salt tolerance characterization and genome-wide association study of Gossypium barbadense accessions reveal salinity-adaptive variations - Li, Huazu; Wang, Shuhui; Zheng, Zhengning; Sun, Yue; Han, Yifei; Xing, Mengyu; Zhang, Tianxu; Mo, Wenlong; Cai, Binbin; Yin, Jinghan; Qian, Jiajie; Muhammad, Uzair; et al. (Frontiers in Plant Science, 2025)
IntroductionAs a globally important cash crop, Gossypium barbadense has the high-quality fiber for textile industry. However, it experiences substantial growth inhibition and yield decline under salt stress, rendering the elucidation of its salt tolerance mechanisms imperative for breeding initiatives.MethodsWe performed population structure analysis on 240 global G. barbadense accessions, phenotyping under salt stress at seedling-stage, genome-wide association study (GWAS), virus-induced gene silencing (VIGS) of Gbar_D02G014670 (GbXTH27), and its functional verification.ResultsPopulation structure analysis on 240 globally distributed G. barbadense accessions resolved four distinct subpopulations. Seedling-stage salt stress screening identified 23 highly salt-tolerant genotypes exhibiting divergent phenotypic responses. GWAS identified multiple significant single nucleotide polymorphism (SNP) loci associated with salt tolerance, with the most prominent signal localized to chromosome D02. VIGS of GbXTH27 exacerbated salt-induced wilting phenotypes and significantly decreased antioxidant enzyme activities.DiscussionThis research provides valuable molecular markers and theoretical foundations for genetic improvement and breeding of salt-tolerant G. barbadense cultivars, while also offering insights into salt stress response mechanisms applicable to other crops.